2017
DOI: 10.1016/j.ecoenv.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of heat shock protein 70 and acetylcholinesterase over a time course suggests environmental adaptation in a foundational molluscan species

Abstract: Waterways in urban areas often act as repositories for sewage, industrial waste, and environmental contaminants. In response, inhabitants of these watersheds undergo physiological adaptations specific to their respective environments. Effects of these stressors can be assayed by quantification of various well-documented biomarkers in sentinel species such as the Atlantic Ribbed mussel, Geukensia demissa, a native to the Bronx River Estuary, Bronx, NY, USA. Heat shock protein 70 (Hsp70) is a universally express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Although some studies observed clear phenotypic upregulation of stress physiological parameters (e.g. GST [33]; Hsp70 [34]), evidence for an evolutionary shift in organismal stress physiology in cities is so far limited (but see [8,14]).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies observed clear phenotypic upregulation of stress physiological parameters (e.g. GST [33]; Hsp70 [34]), evidence for an evolutionary shift in organismal stress physiology in cities is so far limited (but see [8,14]).…”
Section: Introductionmentioning
confidence: 99%
“…The National Oceanic and Atmospheric Administration (NOAA) National Estuarine Eutrophication Survey classifies water quality falling between 2 and 5 mg/L dissolved oxygen as stressed (Bricker et al, 1999). These data indicate that organisms residing in the Bronx River estuary are exposed to chronic, low oxygen levels, a condition that induces stress and metabolic dysfunction (Halem, et al, 2014;Ravaschiere et al, 2017). Table 1.…”
Section: Water Analysesmentioning
confidence: 95%
“…Human activity, industrialization, and climate change continue to negatively impact estuarine ecosystems, especially in urbanized areas (Limburg et al, 2005; Astaraie-Imani et al, 2012; Chin et al, 2013). Estuarine species face stresses associated with adverse environmental conditions such as low dissolved oxygen, combined sewage overflow, toxin contamination, bank destabilization, habitat degradation, and extreme temperature fluctuation (Van Dolah, et al, 2008; Courrat et al, 2009; Halem et al, 2014; Ravaschiere et al, 2017). Knowledge of the molecular mechanisms underlying stress adaptation is essential if we hope to rehabilitate estuarine ecosystems adversely affected by urbanization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adequate genetic diversity is necessary for evolutionary responses to a wide range of urban stressors. A number of studies of rapid evolution to urban stressors indicate organisms are able to adapt quickly due to standing genetic variation (see Reid et al 2017; Wirgin et al., 2011 below), or even more intriguingly, via introgression from other species (Oziolor et al, 2019). Additional experimental evidence indicates the importance of standing variation in adaptation; for example, Nevo, Noy, Lavie, Beiles, and Muchtar (1986) showed that in several pairs of species with differing levels of genetic diversity, the species with greater diversity was found to be more resistant to toxicants.…”
Section: Case Studies: Rapid Adaptation In Urban Marine Ecosystemsmentioning
confidence: 99%